Polarimetry of relativistic tidal disruption event Swift J2058+0516. Issue 2 (6th November 2019) - Wiersema, K; Higgins, A B; Levan, A J; Eyles, R A J; Starling, R L C; Tanvir, N R; Cenko, S B; van der Horst, A J; Gompertz, B P; Greiner, J; Pasham, D R
ABSTRACT: A small fraction of candidate tidal disruption events (TDEs) show evidence of powerful relativistic jets, which are particularly pronounced at radio wavelengths, and likely contribute non-thermal emission at a wide range of wavelengths. A non-thermal emission component can be diagnosed using linear polarimetry, even when the total received light is dominated by emission from an accretion disc or disc outflow. In this paper, we present Very Large Telescope (VLT) measurements of the linear polarization of the optical light of jetted TDE Swift J2058+0516. This is the second jetted TDE studied in this manner, after Swift J1644+57. We find evidence of non-zero optical linear polarization, P_V8 per cent, a level very similar to the near-infrared polarimetry of Swift J1644+57. These detections provide an independent test of the emission mechanisms of the multiwavelength emission of jetted TDEs.